Doing the Word: Southern Baptists' Carver School of Church Social Work and its Predecessors, 1907-1997. By T. Laine Scales and Melody Maxwell. Knoxville: University of Tennessee Press, 2019. xii + 243 pp. $64.00 cloth. - Holcomb, Carol C. (Church history, 2021)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0009640721001372/resource/name/firstPage-S0009640721001372a.jpg